Immunohistochemical Labeling of Low-Density Lipoprotein Receptor and Scavenger Receptor Class B Type 1 Are Increased in Canine Lymphoma - Ceres, Kristina; Fitzgerald, Halle; Quiznon, Kathryn Shanelle; McDonough, Sean; Behling-Kelly, Erica (Frontiers in Veterinary Science, 2019)
Altered lipid metabolism is a well-documented hallmark of neoplastic transformation and impacts disease progression. Two major lipoprotein receptors, the low-density lipoprotein receptor (LDL-R) and scavenger receptor class B, type 1 (SR-BI) are overexpressed in a number of cancer types in people. These receptors serve to deliver cholesterol to the tumor cells and have been used to target drug therapies. In this study, we performed a retrospective analysis of LDL-R and SR-B1 expression in canine lymphoma using archived formalin-fixed tissue samples. Cases were immunophenotyped and classified according to World Health Organization (WHO) standards prior to immunostaining for the LDL_R and SR-B1. A total of 45 cases were evaluated; 21 high grade B (HGB), 11 low grade B (LGB), 7 high grade T (HGT), and 6 low grade T (LGT) lymphomas. One sided Wilcoxon rank sum tests were used to compare staining intensity between neoplastic and hyperplastic lymphoid tissue. The relationships between histological score and tumor grade and score and stage at presentation were assessed using non-parametric Kruskal-Wallis tests. Neoplastic lymphoid tissue expressed higher levels of both receptors compared to reactive lymph nodes. Median LDL-R score was 85.0 (interquartile range = 101.7), Median SR-B1 score was 209.0 (interquartile range 105.2). No relationship between LDL-R or SR-B1 staining score and tumor grade or phenotype was found. Serum cholesterol concentration was compared between dogs with high and low grade tumors using a two sample T-test, and correlations between cholesterol concentration and histological score, and between the score for the two receptors were determined using a Spearman correlation. The high expression level of these lipoprotein receptors on most of the tumors could underlie the lack of relationship between score and tumor grade. The overexpression of LDL-R and SR-B1 in canine lymphoma holds therapeutic potential particularly in dogs that overexpress one or both of these receptors, and this warrants further investigation.